ANALISIS PENENTUAN POLA PRODUKSI UNTUK MEMINIMALISASI BIAYA TAMBAHAN - Miger Nomeni; Christien C. Foenay; Paulina Yuritha Amtiran (Journal of Management Small and Medium Enterprises (SMEs), 2021)
The goal of a company is to achieve optimal results and profits so that the continuity of the company can be maintained. The purpose of this study was to analyze the production patterns used by the Batako Jalan Baru in minimizing additional costs. Data collection techniques used in this study are additional cost analysis techniques using interviews, observation and documentation. This research was conducted in June 2020. The results of the study using three production patterns shows that the most efficient production pattern in minimizing additional costs on the Batako Jalan Baru is a corrugated production pattern because it has the smallest additional costs. The results of this study can provide an alternative choice for companies with the aim of minimizing costs. Keywords: Analysis, Corrugated Production Patterns, Constant Production Patterns, Moderate Production Patterns.